Murtadha Muthahhari - Barsihannor Barsihannor (Al-Hikmah Journal for Religious Studies, 2011)
Murtada Muthahhari is a modern Moslem thinker who has progressive ideas. Beside he was so concern with religious disciplines; he also paid attention to modern thought. His interesting idea deals with historical materialism. In his analysis, he criticized the idea of Karl Marx that considered historical dynamic was determined by economic power, class determinism, and products advancement. According to Muthahhari, Islam views the objective and fate of history together with its evolution as the last struggle on the unbelief. The verse of al-Quran dealing with violence does not mean to settle the universal principles. Those verses do not describe the historical dynamic nor historical mechanism. Muthahhari was on the opinion that history was not only materalism but non materialism as well